Modeling Fragile X Syndrome - Denman, Robert B.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
The present book is an in-depth synopsis of recent advances in the fragile X field. The fragile X syndrome (FXS) is the most common form of inherited mental retardation, and the molecular-genetic basis of this syndrome has been the subject of extensive experimental scrutiny over the last two decades. This book covers the spectrum of current FXS research, ranging from Drosophila model systems via mouse models to clinical and psychiatric aspects. The volume also provides updates on FXS-related diseases such as the fragile X-associated tremor/ataxia syndrome. Significant progress in recent years, as highlighted here by some of the most eminent researchers in the field, are grounds for optimism that successful therapeutical approaches may be feasible in the not too distant future.
Introduction: Reminiscing on Models and Modeling -- Probing Astrocyte Function in Fragile X Syndrome -- Neural Stem Cells -- Fragile X Mental Retardation Protein (FMRP) and the Spinal Sensory System -- The role of the postsynaptic density in the pathology of the fragile X syndrome -- Behavior in a Drosophila model of Fragile X -- Molecular and Genetic Analysis of the Drosophila Model of Fragile X Syndrome -- Fragile X Mental Retardation Protein and Stem Cells -- Manipulating the Fragile Mental Retardation Proteins in the frog -- Exploring the zebra finch Taeniopygia guttata as a novel animal model for the speech-language deficit of fragile X syndrome -- Neuroendocrine alterations in the fragile X mouse -- Taking STEPs forward to understanding Fragile X Syndrome -- Fmr-1 as an offspring genetic and a maternal environmental factor in neurodevelopmental disease -- Mouse Models of the Fragile X Premutation and the Fragile X Associated Tremor/Ataxia Syndrome -- Clinical Aspects of the Fragile X Syndrome -- Fragile X Syndrome: A Psychiatric Perspective -- Fragile X Syndrome and Targeted Treatment Trials -- The Fragile X-associated Tremor Ataxia Syndrome -- Vignettes: Models in Absentia.
Keywords: Life sciences; Human genetics; Gene therapy; Medicine; Cytology; Stem cells; Neurobiology; Life Sciences; Cell Biology; Human Genetics; Molecular Medicine; Neurobiology; Stem Cells; Gene Therapy